Tiger Conservation in India: Past, Present and Future - Melkani, V. K. (Indian Forester, 2001)
Tiger Panthera tigris tigris, our National Animal, is a symbol of our cultural and natural heritage. During the first seven decades of the last century, the population of Tigers in Indian jungles drastically dwindled. Sincere efforts have been made to ensure a safe habitat to the Tiger in the wilderness of Indian jungles. Unfortunately, the threats to the individual and its habitat persist even today. The ongoing efforts need further strengthening with effect control and improved co-ordination among all who are concerned for the survival of Tiger.